Atherosclerosis in Psoriatic Arthritis: A Multiparametric Analysis Using Imaging Technique and Laboratory Markers of Inflammation and Vascular Function - Garg, Nidhi; Krishan, Pawan; Syngle, Ashit (International Journal of Angiology, 2016)
Cardiovascular disease is one of the leading causes of death in psoriatic arthritis (PsA). Pathogenesis of accelerated atherosclerosis in PsA remains to be elucidated. Endothelial dysfunction (ED) often precedes manifesting atherosclerosis. This study aims to assess carotid intima-media thickness (CIMT), a marker of atherosclerosis in PsA, in context of markers of inflammation and vascular function. A cross-sectional study was performed in 18 PsA patients who were compared with 18 controls matched for age and sex. Flow-mediated dilatation (FMD) assessed by AngioDefender (Everist Health, Ann Arbor, MI), endothelial progenitor cells (EPCs) quantified by flow cytometry and CIMT measured ultrasonographically. Inflammatory measures included disease activity score of 28 joints count and disease activity index in psoriatic arthritis. We also assayed markers of inflammation, including C-reactive protein (CRP), erythrocyte sedimentation rate (ESR), proinflammatory cytokines (interleukin [IL]-1, IL-6, and tumor necrosis factor [TNF]-α), and endothelial dysfunction, including lipids, intercellular adhesion molecule 1 (ICAM-1), vascular cell adhesion molecule 1 (VCAM-1), and EPCs. CIMT is significantly higher in PsA patients compared with controls (0.062 ± 0.18 vs. 0.045 ± 0.10 cm, p < 0.01) whereas FMD%, EPCs%, and high-density lipoproteins (HDL) cholesterol are significantly reduced in PsA compared with controls (p < 0.05). Compared with controls, PsA patients had significantly increased concentrations of ESR, CRP, TNF-α, IL-6, ICAM-1, and VCAM-1. In PsA, CIMT positively correlated with IL-6 and ICAM-1 and inversely correlated with FMD, HDL, and EPCs (p < 0.05). In PsA, FMD and CIMT were impaired, indicating endothelial dysfunction and accelerated atherosclerosis, respectively. PsA-related inflammatory mechanisms (TNF-α, IL-6) and markers of vascular function (CRP, ICAM-1, and EPCs) may all be involved in the development of vascular disease in PsA. Cytokine-triggered inflammation upregulates expression of adhesion molecules, depletes EPCs with endothelial dysfunction, and increased CIMT in PsA.
Keywords: adhesion molecules; atherosclerosis; carotid intima-media thickness; endothelial dysfunction; endothelial progenitor cells; inflammatory cytokines; psoriatic arthritis